Original articleImpact of the –174G/C interleukin-6 (IL-6) gene polymorphism on the risk of paediatric ischemic stroke, its symptoms and outcome - Balcerzyk, Anna; Nowak, Marta; Kopyta, Ilona; Emich-Widera, Ewa; Pilarska, Ewa; Pienczk-Ręcławowicz, Karolina; Kaciński, Marek; Wendorff, Janusz; Żak, Iwona (Folia Neuropathologica, 2012)
Objectives : Ischemic stroke remains one of the top ten causes of death in children. There is evidence for the role of pro-inflammatory cytokines, such as IL-6 and the –174G>C promoter polymorphism of the IL-6 gene, in the occurrence and outcome of stroke in adults. The aim of the present study was to determine a possible association between the –174G>C IL-6 polymorphism and occurrence of paediatric stroke, its symptoms and outcome. Material and methods : The study group consisted of 340 individuals: 80 stroke children, 122 parents of patients and 138 controls. The –174G/C polymorphism was genotyped using the RFLP method. For the analysis of the relationship between genotypes and stroke we used two alternative methods: the case-control model and the transmission test for linkage disequilibrium using data from families. Results : We observed no differences in the transmission of alleles from parents to children. We also did not find any statistical differences in distribution of genotypes and alleles between patients and controls. However, the analysis showed that post-stroke epilepsy was genotype-dependent. All children with epilepsy were G allele carriers and none of them was a CC homozygote whereas about 25% of children without epilepsy had the CC genotype. Conclusions : Our study did not show any associations between the IL-6 –174 G>C polymorphism and the occurrence of stroke but we observed a relation between post-stroke epilepsy and the G allele carrier-state.